(untitled) (Italian Journal of Public Health, 2007)
Background: Diet and lifestyle-related factors may be responsible for the different geographical distribution of cardiovascular disease incidence. The aim of our study is to conduct a systematic review of the effect of Mediterranean Diet on cardiovascular diseases (CVD), in terms of prevention of both cardiovascular mortality and cardiovascular events. Methods: We undertook a scientific literature search using MEDLINE, Embase and the Cochrane database for systematic reviews. We selected studies that evaluate the association between mortality and morbidity due to CVD and Mediterranean diet considered as primary or secondary prevention intervention, and found 16 articles concerning 13 studies (2 case-control, 3 cohort studies and 8 randomised clinical trials). Results: The analyzed studies indicate a reduction of adverse cardiovascular events by about 30% and 40%, in terms of primary and the secondary prevention, respectively. Concerning the reduction of mortality, a larger corpus of data is available, demonstrating that the Mediterranean diet significantly reduces mortality by 50% or 70% in terms of secondary prevention, and by about 30% for primary prevention. Conclusions: The Mediterranean diet has positive effects over the CVD both in primary and secondary prevention settings. The estimate of the effect is different in different settings and such variability is attributable to the heterogeneity of the enrolled population, which is obviously lower in the general population compared to those who have already had an adverse cardiovascular event.